Resiliensi Anak yang Berhadapan dengan Hukum di Sentra "Paramita" Mataram Provinsi Nusa Tenggara Barat - Muhamad Ari Purnamaaji; Denti Kardeti; Eri Susanto (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2023)
Children in conflict with the law that undergoing the rehabilitation at Paramita Center cannot live their lives freely, causing feelings of misery, discomfort, boredom, and suffering. This study aims to determine the level of resilience ABH which includes aspects external support, Inner Strength, interpersonal and problem-solving skills. The method used in this study is a quantitative method with a descriptive survey. The sampling in this study used a purposive sampling on 23 ABH. The data collection techniques used were questionnaires, unstructured interviews, and documentation studies. The results showed that the aspect of resilience that gets the highest score is the Inner strength (87,31%), the next is the external support (81,21%) and the last is the interpersonal and problem solving skills (74,78%). Overall, the resilience level of ABH is good, where 2 aspects are in the high category and 1 aspect is in the medium category. The resilience of ABH is very possible to change considering that it is a dynamic process that involves the role of various factors so the researcher recommends a program for Strengthening Resilience of ABH through Self Help Groups.